1995
DOI: 10.1007/bf00666040
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis in breast cancer: Its importance as a prognostic indicator and the association with vascular endothelial growth factor expression

Abstract: The importance of tumor angiogenesis in the process of tumor growth and progression in solid tumors has been widely accepted. We have investigated the significance of tumor angiogenesis as a prognostic indicator in a retrospective study including 328 primary breast cancer patients. The postoperative survey demonstrated that the microvessel density (MVD) evaluated by immunocytochemical staining for factor VIII-related antigen is a potent prognostic indicator. The relapse-free survival (RFS) rate of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
174
4
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(195 citation statements)
references
References 26 publications
13
174
4
4
Order By: Relevance
“…The current study also found that such tumours behaved more aggressively, as they were significantly associated with the presence of LN metastasis (Po0.001), distant metastasis (P ¼ 0.01) and a poorer survival (P ¼ 0.029). These findings are similar to others, both in breast cancer and other tumour types (Toi et al, 1995b;Linderholm et al, 1999;O-Charoenrat et al, 2001). Although the effect of VEGF-A expression can be mediated by an increased vascular network, it should be noted that the growth factor has also been shown to increase breast cancer cell survival through direct action on VEGFR-2 that has been found to be expressed on the surface of the breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study also found that such tumours behaved more aggressively, as they were significantly associated with the presence of LN metastasis (Po0.001), distant metastasis (P ¼ 0.01) and a poorer survival (P ¼ 0.029). These findings are similar to others, both in breast cancer and other tumour types (Toi et al, 1995b;Linderholm et al, 1999;O-Charoenrat et al, 2001). Although the effect of VEGF-A expression can be mediated by an increased vascular network, it should be noted that the growth factor has also been shown to increase breast cancer cell survival through direct action on VEGFR-2 that has been found to be expressed on the surface of the breast cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…The count of positively stained vessels per tumour area, lymph vessel density (LVD), has been used to assess lymphangiogenic characteristics in tumour specimens (Rodriguez-Niedenfuhr et al, 2001;Sahni et al, 2005). High MVD (Weidner et al, 1991;Bevilacqua et al, 1995;Toi et al, 1995b;Choi et al, 2005) and high LVD (Choi et al, 2005) in breast cancer have been reported to be associated with more aggressive tumour behaviour and poorer survival.…”
mentioning
confidence: 99%
“…More importantly, most tumours cannot growth beyond 2‐3 mm 3 without the formation of new blood vessels 22. Breast cancer is a class of angiogenesis‐dependent tumours, and the prognosis of patients with primary tumours is significantly correlated with the extent of angiogenesis 5, 23. Therefore, anti‐angiogenic treatment in combination with chemotherapeutic regimens for breast cancer in preclinical or clinical studies has been under investigation for decades.…”
Section: Discussionmentioning
confidence: 99%
“…They not only promote tumor growth but also play an important role in tumor metastasis. [4][5][6] A number of studies have shown a direct correlation between vascular density in the primary tumor and tumor metastasis to distal sites for patients with cancers of the head-and-neck, 7 breast, 8 prostate, 9 lung, 10 stomach 11 and cervix. 12 Angiogenesis is thought to facilitate tumor metastasis by providing an increased density of immature, highly permeable blood vessels that have little basement membrane and fewer intercellular junctional complexes than normal mature vessels.…”
mentioning
confidence: 99%